Society and the supernatural in Song China - Davis, Edward L. (Honolulu : University of Hawai'i Press, 2001)
Society and the Supernatural in Song China is at once a meticulous examination of spirit-possession and exorcism in the twelfth and thirteenth centuries and a social history of the full panoply of China's religious practices and practitioners at the moment when she was poised to dominate the world economy. Although the Song dynasty (960-1276) is often identified with the establishment of Confucian orthodoxy, Edward Davis demonstrates the renewed vitality of the dynasty's Taoist, Buddhist, and local religious traditions.
Frontmatter -- Contents -- Acknowledgments -- Abbreviations -- 1. Introduction -- 2. Therapeutic Movements in the Song: Texts -- 3. New Therapeutic Movements in the Song: Practitioners -- 4. The Cult of the Black Killer -- 5. The Daoist Ritual Master and Child-Mediums -- 6. Tantric Exorcists and Child-Mediums -- 7. Daoist Priests, Confucian Literati, and Child-Mediums -- 8. Spirit-Possession and the Grateful Dead: Daoist and Buddhist Mortuary Ritual in the Song -- 9. The Syncretic Field of Chinese Religion -- Appendix: Huanglu jiao and Shuilu zhai -- Notes -- Glossary -- Bibliography -- Index -- About the Author.
Includes bibliographical references (pages 329-349) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: China -- Religious life and customs; China -- History -- Song dynasty, 960-1279.; Chine -- Histoire -- 960-1279 (Dynastie des Song); RELIGION -- Eastern; HISTORY -- Asia -- China; Song Dynasty (China); China; Religion; Songdynastie; China; 960-1279; Geschichte 960-1279.; History